1974
DOI: 10.1159/000149965
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Translation of Viral and Cellular mRNA’s in Extracts from Cells Infected with Encephalomyocarditis Virus

Abstract: The relative efficiency of translation of host cell mRNA and encephalomyocarditis (EMC) virus RNA has been investigated in cell-free preparations from un-infected and EMC virus-infected Krebs-II cells. The ability of cell-free extracts from infected cells to translate exogenously-added EMC virus RNA and total Krebs-II cell mRNA was markedly diminished, but no evidence for the selective inhibition of translation of host cell mRNA in these systems was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…To address this apparent discrepancy, we analyzed and translates in a cap-independent fashion, driven by the EMCV internal ribosome entry site) have been used in this study. In accordance with previous studies (22,25,26), all mRNAs tested, regardless of their dependency on the cap for translation, were translated less efficiently in extracts from EMCV-infected than in mock-infected cells. The capdependent globin mRNA translation decreased 2.5-and 8-fold in EMCV R-and EMCV K-2-infected Krebs II ascites translation extracts, respectively, as compared with translation in extracts from mock-infected cells ( Fig.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…To address this apparent discrepancy, we analyzed and translates in a cap-independent fashion, driven by the EMCV internal ribosome entry site) have been used in this study. In accordance with previous studies (22,25,26), all mRNAs tested, regardless of their dependency on the cap for translation, were translated less efficiently in extracts from EMCV-infected than in mock-infected cells. The capdependent globin mRNA translation decreased 2.5-and 8-fold in EMCV R-and EMCV K-2-infected Krebs II ascites translation extracts, respectively, as compared with translation in extracts from mock-infected cells ( Fig.…”
Section: Methodssupporting
confidence: 92%
“…Because eIF4E is necessary for cap-dependent but not for cap-independent translation, its sequestration by 4E-BP1 would be expected to specifically inhibit cap-dependent translation in an in vitro translation extract prepared from EMCVinfected cells. However, numerous earlier studies reported that extracts prepared from EMCV-infected cells did not exhibit any selectivity in cap-independent versus cap-dependent translation (15,22,25,26). These findings are in apparent contradiction with the in vivo data that point to a role for 4E-BP1 in the mediation of the shutoff of host protein synthesis exerted by EMCV.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…In the case of poliovirus infection of HeLa cells a loss of initiation factor activity postulated to be specific for capped mRNA's has been demonstrated (19,36). In contrast, results on encephalomyocarditis (EMC) virus infection of HeLa and other cells have shown that a comparable factor inactivation does not occur (23,27,31,39). Thus, it is clear that the findings from poliovirus-infected cells are not necessarily applicable to other picornavirus infections.…”
mentioning
confidence: 99%